Exploring Children’s Creative Self-Efficacy Affected by After-School Program and Parent–Child Relationships - Liang, Chen-Chu; Yuan, Yu-Hsi (Frontiers in Psychology, 2020)
This study aimed to verify the relationship among children’s creative self-efficacy, parenting style, parent-child relationship, and after-school program. A judgmental sampling was used for subject selection from Taiwan. A total of 550 valid participants were elementary school to junior high school students then their data were put into the statistical process. The multiple regression analysis was applied in this study. The survey tool was developed base on literature review and related articles. Research result supported that the after-school program was the most significant variable that affected the student’s creative self-efficacy. Then the ‘punitive discipline’ and ‘autonomy support’ of the parenting style can affect positive parent-child relationships then it will impact students’ creative self-efficacy. Evidence supported that the ‘negative parent-child relationships’ will not motivate students’ creative self-efficacy. Besides, the after-school program plays an important role in the students’ creative self-efficacy independently.